2014
DOI: 10.1016/j.solener.2014.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the influence of inclination angle and wind on the heat losses of cavity receivers for solar thermal power towers

Abstract: The convective heat losses of cavity receivers for solar thermal power towers are of great importance for the overall efficiency of the whole system. However, the influence of wind on these losses has not been studied sufficiently for large scale cavity receivers with different inclination angles. In this present study the impact of head-on and side-on wind on large cavity receivers with inclination angles in the range of 0 • (horizontal cavity) to 90 • (vertical cavity) is analyzed numerically. The simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 9 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Samanes et al [18] compared different correlations for convective losses prediction and selected the Clausing's approach. A numerical analysis of convective losses of inclined cavity was proposed in [19]. They concluded that in no wind condition the Clausing model and the simulation results match very well (for both horizontal and inclined cavities).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Samanes et al [18] compared different correlations for convective losses prediction and selected the Clausing's approach. A numerical analysis of convective losses of inclined cavity was proposed in [19]. They concluded that in no wind condition the Clausing model and the simulation results match very well (for both horizontal and inclined cavities).…”
Section: Contextmentioning
confidence: 99%
“…Negligible mixing occurs with the stagnant zone due to the change of the air density with temperature. According to [19], the Clausing's model allows evaluating the natural convection in the cavity. However, in the case of forced convection, i.e., when there is some wind, the cavity is split into three zones, stagnant and strong convection zones, as in the Clausing's model, but also with an intermediary transition zone, whose thickness depends on the aperture inclination and the wind velocity.…”
Section: Convective Lossesmentioning
confidence: 99%
“…The boundary conditions of the inner surface of the cavity have often been simplified in different ways by many researchers. Flesch et al [3] and Xiao et al [4] did not consider the helical tube in the cavity when exploring the effects of wind on the thermal performance of the receiver. Their models were greatly simplified.…”
Section: Introductionmentioning
confidence: 99%
“…Flesch et al [19] numerically analyzed the impact of head-on and sideon wind on large cavity receivers with inclination angles ranging from 0°(horizontal cavity) to 90°(vertical cavity) and compared with the data published in the open literature. Yu et al [20] performed a numerical investigation on the heat transfer characteristics of the porous material used in the receiver of a CSP with different structure parameters.…”
Section: Introductionmentioning
confidence: 99%